Aid for War? An Empirical Assessment of Donor Interventions in Civil Wars - Tobias Lechtenfeld (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
Since 1960 foreign aid to countries with civil war has exceeded 300 billion in Sub-Saharan Africa alone. Using a global panel of more than 150 civil wars between 1945 and 2000, this paper evaluates the impact of diplomatic, military and economic interventions on conflict duration. Moreover, specific conditions are identified under which foreign interventions work best. The results suggest that diplomatic and military interventions can shorten civil wars, while economic interventions do not affect the duration of civil wars but may play a conditioning role. The findings are obtained by fitting a proportional hazard model for time-varying covariates. They are confirmed using a logit model, which is then expanded for additional robustness checks.
Keywords: 330; Aid; Civil War; Interventions; Duration Analysis; Cox; Logit; Heterogeneity